Estimating the spatial distribution and locating hotspots of forest biomass from harvest residues and fire-damaged stands in Canada's managed forests. (February 2017) - Mansuy, Nicolas; Paré, David; Thiffault, Evelyne; Bernier, Pierre Y.; Cyr, Guillaume; Manka, Francis; Lafleur, Benoit; Guindon, Luc
Abstract: Strategies for increasing the mobilization of forest biomass supply chains for bioenergy production require continuous assessments of the spatial and temporal availability of biomass feedstock. Using remote sensing products at a 250-m pixel resolution, estimates of theoretical biomass availability from harvest residues and fire-killed trees were computed by combining Canada-wide maps of forest attributes (2001) and of yearly (2002–2011) fires and harvests. At the national scale, biomass availability was estimated at 47 ± 18 M ODT year −1 from fire-killed trees and at 14 ± 2 M ODT year −1 from harvest residues. Mean biomass densities in burned and harvested pixels were estimated at 34 ± 3.0 ODT ha −1 and at 24 ± 1.2 ODT ha −1, respectively. Mean biomass densities also varied dramatically among ecozones, from 14 ODT ha −1 to 206 ODT ha −1 and from 6 ODT ha −1 to 63 ODT ha −1 for burned and harvested pixels, respectively. Spatial averaging with a 100-km radius window shows distinct hotspots of biomass availability across Canada. The largest hotspots from fire-killed trees reached 3.6 M ODT year −1 in the Boreal Shield and the Boreal Plains ecozones of northern Alberta and Saskatchewan, where fires are large and frequent. The largest hotspots from harvest residues reached 1.2 M ODT year −1 in the Montane Cordillera ecozone of British Columbia. The use of spatially explicit remote sensing products yields estimates of theoretical biomass availability that are methodologically consistent across Canada. Future development should include validations with on-the-ground forest inventories as well as the factoring in of environmental, technical and economic considerations to implement operational biomass supply chains. Highlights: Salvage logging of fire-killed stands yields more biomass than the retrieval of harvest residues. Biomass available from fires shows greater annual variability relative to biomass from harvest residues. Largest hotspots of biomass from fire-killed stands are located in the northern part of the managed forest. Validation with in situ forest operations at the stand scale would increase confidence in our methodology.